2012
DOI: 10.1002/adfm.201103074
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction Engineering of CdTe and CdSe Quantum Dots on TiO2 Nanotube Arrays: Intricate Effects of Size‐Dependency and Interfacial Contact on Photoconversion Efficiencies

Abstract: The quality of heterojunctions at the quantum dot (QD)‐TiO2 nanotube (TNT) interface has important implications on the efficiencies of photoelectrochemical solar cells. Here, it is shown that electrophoretic deposition of pre‐synthesized thioacid‐capped CdTe QDs results in relatively poor charge transfer across the heterojunctions. This is likely due to the intermediate layer of bifunctional linkers (S‐R‐COOH) in between the QDs and TNT. On the other hand, CdTe QD‐sensitized TNT prepared by in situ deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 39 publications
4
78
0
Order By: Relevance
“…Recently, coupling of the anodized TNTs with narrow band gap semiconductors, such as CdS [13][14][15][16], CdSe [17][18][19], and PbS [20][21][22], have been utilized to improve the photoresponse of TNTs in the visible light region. Under visible light irradiation, these narrow band gap semiconductors can act as sensitizers and facilitate the photoexcited electrons flow from their CB to the CB of TNTs due to that the CB of these semiconductors is higher than that of TNTs, therefore assisting charge separation and improving visible-light-driven PC activity of the TNTs based nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, coupling of the anodized TNTs with narrow band gap semiconductors, such as CdS [13][14][15][16], CdSe [17][18][19], and PbS [20][21][22], have been utilized to improve the photoresponse of TNTs in the visible light region. Under visible light irradiation, these narrow band gap semiconductors can act as sensitizers and facilitate the photoexcited electrons flow from their CB to the CB of TNTs due to that the CB of these semiconductors is higher than that of TNTs, therefore assisting charge separation and improving visible-light-driven PC activity of the TNTs based nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in the field showed that semiconductor quantum dots (QDs) could effectively sensitize wide band gap metal oxides instead of organic dyes [12]. Semiconductor QDs in the form of very small crystals could be very stable while present the advantage to match solar spectrum better because their absorption spectrum can be tailored by size quantization [13,14]. Moreover, the possibility of generation of multiple electronehole pairs from one photon could lead to very high theoretical efficiencies exceeding 66% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the semiconductor quantum dots (QDs), such as CdS, CdSe, CdTe, PbS, etc. have been employed as a sensitizer to fabricate the high efficient quantum dot sensitized solar cells (QDSSCs) due to their large absorption edge, high extinction coefficients, ultrafast electron transfer, quantum size effect and multiple electron-hole pairs generation [3][4][5][6][7][8][9]. Furthermore, the ternary chalcopyrite with their low toxicity and excellent optical properties has been attracted significant attention in photovoltaic devices [10].…”
Section: Introductionmentioning
confidence: 99%